2021
DOI: 10.1172/jci.insight.141962
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-derived extracellular vesicles regulate survival and function of pancreatic β cells

Abstract: Extracellular vesicles (EVs) are implicated in the crosstalk between adipocytes and other metabolic organs, and an altered biological cargo has been observed in EVs from human obese adipose tissue (AT). Yet, the role of adipocyte-derived EVs in pancreatic β cells remains to be determined. Here, we explored the effects of EVs released from adipocytes isolated from both rodents and humans and human AT explants on survival and function of pancreatic β cells and human pancreatic islets. EVs from healthy 3T3-L1 adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 55 publications
6
64
0
Order By: Relevance
“…Generally, AT can influence PDAC development systemically via soluble mediators that are released from distant (visceral) fat depots and reach the pancreatic microenvironment through the systemic circulation or via paracrine effects elicited by intrapancreatic adipocytes (see below) [63,64]. A mechanism that is receiving increasing attention is communication via extracellular vesicles from adipocytes that can fuse with target cells in the pancreas [65][66][67]. It has been shown recently that adipocytes experience strong energetic stress during obesity, which resulted in the release of small extracellular vesicles harboring respiration-competent, but oxidatively damaged, mitochondrial fragments, which access the systemic circulation and are internalized by cardiomyocytes [68].…”
Section: Adipose Tissue and Obesity-associated Meta-inflammationmentioning
confidence: 99%
“…Generally, AT can influence PDAC development systemically via soluble mediators that are released from distant (visceral) fat depots and reach the pancreatic microenvironment through the systemic circulation or via paracrine effects elicited by intrapancreatic adipocytes (see below) [63,64]. A mechanism that is receiving increasing attention is communication via extracellular vesicles from adipocytes that can fuse with target cells in the pancreas [65][66][67]. It has been shown recently that adipocytes experience strong energetic stress during obesity, which resulted in the release of small extracellular vesicles harboring respiration-competent, but oxidatively damaged, mitochondrial fragments, which access the systemic circulation and are internalized by cardiomyocytes [68].…”
Section: Adipose Tissue and Obesity-associated Meta-inflammationmentioning
confidence: 99%
“… 344 MiRNAs profiles in adipocyte-derived exosomes vary under different physiopathological conditions of adipose tissue. 345 Adipocyte-derived exosomal miRNAs, such as miR-34a, 346 miR-222, 347 miR-27a, 348 and miR-802-5p 85 can promote IR via regulating Krüppel-like factor 4 (KLF4), insulin receptor substrate 1 (IRS1), peroxisome proliferator-activated receptor γ (PPARγ), and HSP60. Hepatocyte uptake of exosomes from adipocytes in obese mice containing less miR-141-3p than that in healthy mice, and the reduced absorption of miR-141-3p resulted in reduced glucose uptake in hepatocytes.…”
Section: The Roles Of Exosomal Ncrnas In Human Diseasesmentioning
confidence: 99%
“…Recently, Gesmundo et al. reported that adipocyte-derived EVs regulated the survival and function of human pancreatic β cells and pancreatic islets ( 164 ). For the role of EVs in islet transplantation, readers are encouraged to refer to the prior review ( 165 ).…”
Section: Therapeutic Potentials Of Stem Cell-derived Evs For Overcoming the Shortage Of Islet Beta Cells In T1dmentioning
confidence: 99%